The Evolving Food Situation - Paulino, Leonardo A. (International Food Policy Research Institute, 1987)
Over the past two decades, of all the major regions of the Third World, sub-Saharan Africa has had the most rapid growth of population and the slowest growth of food output.' And its population growth rate has accelerated, while the food production growth rate has decelerated. For the Third World as a whole, production of major food crops outpaced population growth by more than a half percentage point per year over the past two decades, while in sub-Saharan Africa the food production growth rate was a full percentage point short of its population growth rate. Food production growth has depended more on growth in crop area and labor force and much less on yield increase and modern inputs compared to other parts of the world. Thus African agriculture is characterized by poor and deteriorating performance and little modernization.